Reframing Strategic Marketing Management for Islamic Educational Institutions in the Digital Era - Bahri, A. Saeful; Napsin, Napsin; Maryati, Nenden; Kasetyaningsih, Sufia Widi; Nashrulloh, Yusuf; Jaelani, Mahpud (Global Education Journal, 2025)
Declining student enrollment has become a critical challenge for Islamic educational institutions in maintaining institutional continuity and educational quality, including SMP Qur'an As-Salam. The purpose of this study is to examine the implementation of marketing management through the Planning, Organizing, Actuating, and Controlling (POAC) framework to enhance institutional attractiveness and public image. This study used a descriptive qualitative methodology, with data collected through in-depth interviews, direct observation, and document analysis. Participants included school leaders, administrative staff, teachers, and parents directly involved in marketing-related activities. Data were analyzed using data reduction, data presentation, and conclusion formulation, while data validity was ensured through source and methodological triangulation. The findings of this study indicate that SMP Qur'an As-Salam's marketing planning aligns with its Qur'anic vision and mission, emphasizing Islamic character development, a Qur'an memorization program, and academic excellence. Promotional practices integrate direct outreach activities such as community engagement, brochures, banners, and social events with digital platforms, including social media, websites, and educational content. Therefore, continuous innovation, digital marketing capacity building, and collaborative partnerships are recommended to strengthen sustainability in the digital era.